2022
DOI: 10.13189/saj.2022.100205
|View full text |Cite
|
Sign up to set email alerts
|

University Students' Daily Activities and Physical Fitness during COVID-19 Pandemic

Abstract: This study aims to evaluate university students' daily activities and the effect of physical activity on physical fitness, especially during the COVID-19 pandemic. This research used comparative and correlational research methods. Thirty research samples consisted of 13 junior year university students and 17 senior year university students were selected by the purposive sampling method. Every student was monitored for their daily activities for one week and categorized into sports, college, organization, and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
0
1
0
2
Order By: Relevance
“…[17]. In comparison to the findings on gender difference and exercise, Panenggak and colleagues [18] confirmed that male students spent more time exercising than female students during the pandemic. Another study in the Philippines found that lack of time was a factor that caused inactivity [19].…”
Section: Introductionmentioning
confidence: 86%
“…[17]. In comparison to the findings on gender difference and exercise, Panenggak and colleagues [18] confirmed that male students spent more time exercising than female students during the pandemic. Another study in the Philippines found that lack of time was a factor that caused inactivity [19].…”
Section: Introductionmentioning
confidence: 86%
“…Temuan dari penelitian ini berbeda dari penelitian-penelitian sebelumnya yang menunjukkan kebugaran mahasiswa masa pandemi Covid-19 pada kategori sedang (Sinuraya et al, 2022). Perbedaan hasil penelitian ini terjadi karena tingkat kebugaran berhubungan dengan dengan aktivitas fisik dan kegiatan sehari-hari, sehingga walaupun aktivitas pembelajaran dilakukan secara daring dan pembatasan kegiatan sosial di luar rumah tetapi kegiatan mahasiswa di rumah masih dilakukan seperti biasa yang memungkinkan untuk tetap menjaga tingkat kebugaran pada kategori sedang maupun baik sekali (Panenggak et al, 2022). Pada masa pandemi Covid-19 berbagai pembatasan kegiatan masyarakat mempengaruhi kesehatan psikologis dan ketergantungan pada media sosial dan menghabiskan waktu luang.…”
Section: Metode Penelitianunclassified
“…Tingkat kebugaran fisik yang rendah dikaitkan dengan kesehatan fisik dan mental yang rendah (Woutersetal., 2020). Sebaliknya, tingkatkebugaranjasmani yang baik selalu berkaitan dengan tingkat aktivitas fisik aktif (Panenggak et al, 2022).Variabel Kebugaran jasmani juga berhubungan dengan rendahnya tingkat kelenturan pada remaja, misalnya kelebihan berat badan, dan rendahnya tingkat kebugaran aerobik dan kekuatan otot (Mendiasetal., 2017). Profil kebugaran fisik yang lebih baik termasuk fleksibilitas, kekuatan fungsional, dan kecepatan kelincahan berlari menjelaskan peningkatan selanjutnya dalam prestasi akademik (Gouveiaetal., 2020).…”
Section: Poin Dan Gameunclassified